Characterization of Niemann-Pick Type C2 protein expression in multiple cancers using a novel NPC2 monoclonal antibody. - Yi-Jen Liao (Public Library of Science (PLoS), 2013)
Niemann-Pick Type C2 (NPC2) plays an important role in the regulation of intracellular cholesterol homeostasis via direct binding with free cholesterol. However, little is known about the significance of NPC2 in cancer. In this study, we have pinpointed the impact of various different cancers on NPC2 expression. A series of anti-NPC2 monoclonal antibodies (mAbs) with the IgG2a isotype were generated and peptide screening demonstrated that the reactive epitope were amino acid residues 31-40 of the human NPC2 protein. The specificity of these mAbs was confirmed by Western blotting using shRNA mediated knock-down of NPC2 in human SK-Hep1 cells. By immunohistochemical staining, NPC2 is expressed in normal kidney, liver, breast, colon, lung, esophageal, uterine cervical, pancreatic and stomach tissue. Strong expression of NPC2 was found in the distal and proximal convoluted tubule of kidney and the hepatocytes of liver. Normal esophageal, uterine cervical, pancreatic, stomach, breast, colon and lung tissue stained moderately to weakly. When compared to their normal tissue equivalents, NPC2 overexpression was observed in cancers of the breast, colon and lung. Regarding to breast cancer, NPC2 up-regulation is associated with estrogen receptor (-), progesterone receptor (-) and human epidermal growth factor receptor (+). On the other hand, NPC2 was found to be down-regulated in renal cell carcinoma, liver cirrhosis and hepatoma tissues. By antigen-capture enzyme immunoassay ELISA, the serum NPC2 is increased in patients with cirrhosis and liver cancer. According to western blot data, the change of glycosylated pattern of NPC2 in serum is associated with cirrhosis and liver cancer. To the best of our knowledge, this is the first comprehensive immunohistochemical and serological study investigating the expression of NPC2 in a variety of different human cancers. These novel monoclonal antibodies should help with elucidating the roles of NPC2 in tumor development, especially in liver and breast cancers.